IT-graduate abilities: Performance gap as an input for curriculum improvement - Jamaludin, Zulikha; Abdul Mutalib, Ariffin (2010 IEEE, 2005)
This paper reports one of the initiatives done by the Faculty of Information Technology, Universiti Utara Malaysia in its efforts to improve the IT curriculum, The initiative generates a survey focusing on the employers’ perception towards the performance of IT graduates in their workplace. Nineteen IT-related elements have been put forward for evaluation in terms of importance and performance. The evaluation has three objectives namely, (1) gathering the employers’ perceptions using questionnaires and interviews, (2) identifying the competency gap between the performance of our graduates as compared to the importance of the identifed elements, and (3) proposing steps for improving the IT curriculum in the BIT programme in preparing graduates that are both knowledgeable and marketable. In this paper, we reported the obtained results, the analysis that can be drawn from the results, and the possible action that can be taken to improve the BIT programme.